Allergology in Europe, the blueprint. Issue 10 (21st September 2013) - de, J. G.; Demoly, P.; Akdis, C. A.; Cardona, V.; Papadopoulos, N. G.; Schmid‐Grendelmeier, P.; Gayraud, J.
Abstract The number of patients with allergic diseases in Europe, and thus relevant demand for health care, is continuously increasing. In this EAACI‐UEMS position paper, a rationale is given for the medical specialty of allergology. General practitioners and general paediatricians usually cannot elucidate and address all causative factors. Throughout Europe, therefore, the expertise of allergologists (allergists) is required. In collaboration with other medical professionals, they take care of allergic patients, in private practices or in specialized public centres. A well‐structured collaboration between allergists and allergy centres offers the possibility of rapid signalling of new trends developing in the population of allergic patients (e.g. in food and drug allergy). Allergy centres also can perform clinical (and basic) research, teach medical students, future allergists and provide postgraduate training. To prevent that the quality of care in one or several countries within Europe lags behind developments in other countries, the UEMS Section and Board on Allergology together with the European Academy of Allergy and Clinical Immunology advocates the status of a full specialty of allergology in each European country, with a further intention to align their activities (blueprint, curriculum and centre visitation) with the UEMS Section of Paediatrics.